THE ROLE OF ENGLISH IN SPREADING ISLAM RAHMATAN LIL ‘ALAMIN VALUES: MILLENNIALS’ VOICES - Setyaningrum, Anisah; Rochanah, Rochanah (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
The rapid development of Islam in the world cannot be separated from the role of the international language. Islam, a Rahmatan lil 'Alamin religion, has a negative stigma in the international world. Millennials are young people who are very attached to information technology. Therefore, this paper aims to examine the voice of millennials more deeply toward the role of English in the spread of Islam Rahmatan lil 'Alamin values full of affection and peace. This study is qualitative research with a phenomenological approach. The data were collected by conducting semi-structured interviews. The results showed that millennials' voices toward the role of language are: ease of communication, medium of communication, and ease the information access. Then, millennials' voices toward the role of English in the spread of Islam Rahmatan lil 'Alamin values are: ease the convey Islam Rahmatan lil 'Alamin values through various fields, expand the reach of areas and targets in the spread of the values, ease in obtaining information about the spread of the values which can be accessed on the internet, supports efforts to straighten out the negative stigma directed at Islam and ease capturing messages about the values from various sources.  The research implications suggest that leveraging English as a medium can significantly enhance the dissemination of Islam's values of compassion and peace among global audiences, particularly through digital platforms, thereby fostering greater understanding and reducing negative stereotypes associated with Islam.